Upaya Perubahan Undang-Undang Nomor 42 Tahun 1999 Tentang Jaminan Fidusia - Yelia Natasya Winstar; Devie Rachmat Ali Hasan R (Perspektif Hukum, 2015)
The Fiduciary Act should provide legal protection of the parties and legal certainty, but on the other hand there are still some weaknesses of the Fiduciary Act. This paper analyzes the weaknesses of Act Number 42 Year 1999 on Fiduciary and the need for revising the Act. The type of research is a normative legal research or library which includes a study of the principles of law and the systematics of law. The research uses the statute approach and the conceptual approach. Based on the analysis it can be concludde that it requires to revise the Fiduciary Act. Legislators should produce the law not only ensuring the legal certainty but they also can provide the law presenting justice and prosperity for the people. Revision of the Fiduciary Act is expected to provide maximum protection to the people who use the fiduciary as a guarantee agency; so that the justice will be obtained by the people to create a conducive atmosphere in the economy to increase the prosperity for them.